Scientific Substantiation of the Use of the Environmentally Safe Water-Saving Irrigation System in the Conditions of the Insufficient Wet Area of Azerbaijan. (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2019)
It should be recognized that the Republic of Azerbaijan has a leash of 14% of the water supply in the whole of Transcaucasia. Then, when the interim water balance of the republic is 32.29 million km3. However, in the best case, the water years with a 95% supply due to neighboring water atheria, this figure reaches up to 20 million km , as well as in shallow years, the republic will only reduce it to 17.0 million km3. water. That is, there is an acute shortage of water in the country. For the rational use of already limited water resources, it is necessary to switch to modern progressive irrigation methods using small-scale mechanization and automation of irrigation. The current technical equipment for irrigation does not always meet the requirements of the specific conditions of Azerbaijan. Our proposed irrigation system can be successfully used in various soil, climatic and difficult geographic conditions in the country, which was tested in the country with certifying indicators as crop yields increased to 38-50%, when irrigation water of 3 or more was saved times, while maintaining the ecological balance of the environment.